FEATURES OF DEMOCRATIC TRANSIT PROCESS IN UKRAINE AND THE REPUBLIC OF MOLDOVA - Назаров, М.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
In the article the features of transformation processes are considered in two post-communist states. Pre-conditions of this transition, process of transition, problems and results are analyzed. Attention was emphasized on the transformation processes of society, the role of citizens in the state and their influence on the acceptance of political decisions.